Penerapan konseling kelompok dengan pendekatan behavioral untuk meningkatkan kemampuan prestasi belajar siswa madrasah tsanawiyah - Anggina, Asih; Lubis, Saiful Akhyar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This research aims to find out how to apply group counseling with a behavioral approach to improve the learning achievement abilities of class VII students at MTS TPI Medan. This research uses quantitative. The method used in this research is one group pre-test and post-test design. The population in this study was all 60 class VII students. The research sample consisted of 9 students. The data collection tool is a learning achievement questionnaire whose validity has been tested using SPSS 29.0. From the results of the t test in the form of a paired sample test, learning achievement ability is in the high category with an average value (mean) of 16.88889 and also shows that there is a significant value of <.001, meaning less than 0.05, it can be concluded that H0 is rejected. So it can be said that there is a significant difference between learning achievement abilities before and after implementing group counseling with a behavioral approach.